Implementation of Legal Principles of Agreement Between Policyholders and Insurance Companies - Markus Gunawan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The implementation of the legal regulation of the principle of the agreement between the policyholder and the insurance company is law no. 40 of 2014 concerning insurance and the Civil Code, article 1320 on the terms of a legal agreement, commercial law books, article 246, the meaning of insurance, and the provisions of the article in an insurance policy. Limiting factors in submitting claims, namely, failing to fulfill administrative requirements and ignorance of customers with the benefits purchased. The principle of implementing the law of the agreement between the policyholder and the insurance company at PT. Batam branch Sequis Life Life Insurance. With the construction problem: -how is the law determining the implementation of agreements between policyholders and insurance companies with one of the factors hindering filing claims in the PT Asuransi Jiwa Sequis Life Batam branch? Qualification/writing in this type of journal uses normative legal writing and legal research supported by sociological/empirical nonprofits. To analyze the problems in this journal, Jeremy Bentham's theory (theory) of utilitarianism is used, the middle theory (middle theory) by Roscoe Pound law as a social engineering tool, theory and application (Applied theory) by Philip Nonet and Philip Selznick, namely essential law society.